Pengaruh Penggunaan Media Roulette Angka Terhadap Kemampuan Kognitif Anak dalam Mengenal Lambang Bilangan pada Kelompok B Usia 5-6 Tahun TK Pelangi Medan T.A 2023/2024 - Hutasoit, Sherina; Handayani, Peny Husna (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2024)
The results of this study indicated that there was a difference in the level of cognitive ability of children in recognizing number symbols in Group B, aged 5-6 years, at TK Pelangi Medan, where learning activities were conducted using number roulette media. The children were given 2 treatment periods using the number roulette media and 2 treatment periods without using the roulette media. In the first period (X1O1), children who received treatment scored an average of 9.43, which falls into the fairly good category. In the second period (X0O2), without treatment using the roulette media, the children scored an average of 6.12, which falls into the less good category. In the third period (X1O3), children who received treatment scored an average of 17.62, which falls into the very good category, and in the fourth period (X0O4), without treatment using the roulette media, the children scored an average of 14.37, which falls into the good category.The data scores indicate that the use of number roulette media has a significant effect on the cognitive ability of children in Group B, aged 5-6 years, at TK Pelangi in recognizing number symbols. This is evidenced by the SPSS output, which shows that the Asymp. Sig (2-tailed) value is 0.000. Since the value 0.000 is less than 0.005, Ha is accepted, meaning there is a significant difference in the average learning outcomes before and after treatment. Therefore, it can be said that